Reporting recommendations for tumor marker prognostic studies (REMARK): explanation and elaboration. - Altman, D; McShane, L; Sauerbrei, W; Taube, SE (BioMed Central, 2012)
The Reporting Recommendations for Tumor Marker Prognostic Studies (REMARK) checklist consists of 20 items to report for published tumor marker prognostic studies. It was developed to address widespread deficiencies in the reporting of such studies. In this paper we expand on the REMARK checklist to enhance its use and effectiveness through better understanding of the intent of each item and why the information is important to report.